Investigation of Finite Element Model of Futsal Ball and Simulation of its Impact Characteristics. - Fabian Halley Pata, Alban Dattu (2019)
Futsal is gradually becoming the world’s favourite game. Due to increasing technological advancement and demand for performance, ball manufacturers have progressively been introducing new designs over the years. Enhanced performance is essential to make sports equipment as user-friendly as possible to avoid injuries. To date, there is much controversy on the effects of the severity of ball impact to the head. The attention is on the repetitive heading tactics used by younger generations. This study aims to investigate the Finite Element model of the sizefour futsal balland the impact between a ball and a rigid surface to predict the dynamic properties of the ball during impact. A drop test impact experiment involves the measurement of the Coefficientof Restitution (COR), deformation, and contact time. A video camera in high-speed mode and a motion sensor are employedto measure the characteristics during impact. The Solidworks software is employed for modelling and simulation of the drop test impact experiment. The COR values reduce as the drop height is increased,while deformation and contact time increase as the drop height increases. The report shows that energy losses during impact increases as the drop height increased, it was showed by the increasing deformation of the futsal ball in each drop height. The three types of materials used for comparison are butyl, latex, and natural rubber. From the simulation, butyl is the most suitable material for the development of the futsal ball, as butyl rubber showed the minimum stress (0.082 N/m2) and deformation (10612 mm) for each drop height. Natural rubber showed the highest stress (193.851 N/m2) and deformation (2.950 mm) for all drop cases.